Female-dominant estrogen production in healthy children before adrenarche. Issue 10 (28th September 2021) - Igarashi, Maki; Ayabe, Tadayuki; Yamamoto-Hanada, Kiwako; Matsubara, Keiko; Sasaki, Hatoko; Saito-Abe, Mayako; Sato, Miori; Mise, Nathan; Ikegami, Akihiko; Shimono, Masayuki; Suga, Reiko; Ohga, Shouichi; et al.
Abstract : Objective: Ultra-sensitive hormone assays have detected slight sex differences in blood estradiol (E2 ) levels in young children before adrenarche. However, the origin of circulating E2 in these individuals remains unknown. This study aimed to clarify how E2 is produced in young girls before adrenarche. Design: This is a satellite project of the Japan Environment and Children's Study organized by the National Institute for Environmental Studies. Methods: We collected blood samples from healthy 6-year-old Japanese children (79 boys and 71 girls). Hormone measurements and data analysis were performed in the National Institute for Environmental Studies and the Medical Support Center of the Japan Environment and Children's Study, respectively. Results: E2 and follicle stimulating hormone (FSH) levels were significantly higher in girls than in boys, while dehydroepiandrosterone sulfate (DHEA-S) and testosterone levels were comparable between the two groups. Girls showed significantly higher E2 /testosterone ratios than boys. In children of both sexes, a correlation was observed between E2 and testosterone levels and between testosterone and DHEA-S levels. Moreover, E2 levels were correlated with FSH levels only in girls. Conclusions: The results indicate that in 6-year-old girls, circulating E2 is produced primarily in the ovary from adrenal steroids through FSH-induced aromatase upregulation. This study provides evidence that female-dominant E2 production starts several months or years before adrenarche. The biological significance of E2 biosynthesis in these young children needs to be clarified in future studies.